Long‐term functional and survival outcomes after induction chemotherapy and risk‐based definitive therapy for locally advanced squamous cell carcinoma of the head and neck. Issue 4 (18th June 2013) - Hutcheson, Katherine A.; Lewin, Jan S.; Holsinger, F. Christopher; Steinhaus, Ganene; Lisec, Asher; Barringer, Denise A.; Lin, Heather Y.; Villalobos, Sandra; Garden, Adam S.; Papadimitrakopoulou, Vali; Kies, Merrill S.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to evaluate long‐term outcomes after induction chemotherapy followed by "risk‐based" local therapy for locally‐advanced squamous cell carcinoma of the head and neck (SCCHN). Methods Forty‐seven patients (stage IV; ≥N2b) were enrolled in a phase II trial. Baseline and 24‐month functional measures included modified barium swallow (MBS) studies, oropharyngeal swallow efficiency (OPSE), and the MD Anderson Dysphagia Inventory (MDADI). Functional status was assessed at 5 years. Results Five‐year overall survival (OS) was 89% (95% confidence interval [CI], 81% to 99%). A nonsignificant 13% average reduction in swallowing efficiency (OPSE) was observed at 24 months relative to baseline (p = .191). MDADI scores approximated baseline at 24 months. Among 42 long‐term survivors (median, 5.9 years), 3 patients (7.1%) had chronic dysphagia. The rate of final gastrostomy dependence was 4.8% (2 of 42). Conclusion Sequential chemoradiotherapy achieved favorable outcomes among patients with locally advanced SCCHN, mainly of oropharyngeal origin. MBS and MDADI scores found modest swallowing deterioration at 2 years, and chronic aspiration was uncommon in long‐term survivors. © 2013 Wiley Periodicals, Inc. Head Neck36: 474–480, 2014